Numerical simulation and experimental study of two-phase flow in downhole spiral gas-liquid separator - Li, Chenghua; Li, Zhiping; Zhang, Yangyang; Li, Bing (Frontiers in Earth Science, 2023)
Gas-liquid separator is an important surface equipment in oilfield development. Improving the separation efficiency of separator is of great significance to the overall economic benefit of oilfield. Spiral separator is a high efficiency separation device that has been widely used, but at present, there are not enough studies on separation efficiency in number of spiral turns and pitches. In view of this problem, this paper analyzed the gas–liquid separation efficiency of spiral separators with different number of spiral turns and pitches via the fluent numerical simulation software and laboratory experiments. The results showed that a greater number of spiral turns and a larger particle diameter could lead to higher separation efficiency. The separation efficiency has an optimum value for the pitch. The performance of the downhole spiral separator was verified by laboratory experiments, and the separation efficiency was above 90% under the conditions where the treatment amount was either unchanged or changed. These results can provide a reference for the application of spiral separators in oil fields.